Settlement of Banking Credit Facility Disputes Through a Simple Lawsuit (Case Study Case Number 9/Pdt.G.S/2021.PN.Pin) - Tahir, Muhammad Fadil; Khalid, Hasbuddin; Sunusi, Sudirman; Tarring, Anisah Daeng (Faculty of Law, Universitas Muslim Indonesia, 2024)
This study aims to analyze the mechanism for resolving bank credit facility disputes through a simple lawsuit in the District Court of Pinrang and to understand the form of responsibility carried out by the debtor to the creditor in resolving bank credit facility disputes through a simple lawsuit in the District Court of Pinrang. This research is empirical research, namely research that is conducted directly into the field in order to obtain complete data regarding the mechanism for resolving bank credit facility disputes through a simple lawsuit in the Pinrang District Court. The results of the study show that the settlement of bank credit facility disputes through a simple lawsuit with case number 9/Pdt.G.S/2021/PN.Pin at PT. BANK MEGA.Tbk. Choose the path of dispute resolution through the path of peace. In practice, when the debtor makes bad credit, PT. BANK MEGA.Tbk, can execute on the basis of an agreement. The execution was carried out by: First, it was carried out by subpoena three times. Second, the execution is carried out directly under the hands of the object that is the object of collateral without going through a lawsuit in a district court. Third, direct execution through a public auction where the results of the auction are taken to pay off the payment of receivables. Direct executions can be carried out without involving the court. If underhand sales reach the highest price that benefits the parties, then the fiduciary guarantee dispute resolution is relevant to the applicable law. Abstrak Peneltian ini bertujuan untuk menganalisis mekanisme penyelesaian sengketa fasilitas kredit perbankan melalui gugatan sederhana di pengadilan negeri pinrang dan memhami bentuk tanggungjawab yang dilakukan oleh debitur terhadap kreditur pada penyelesaian sengketa fasilitas kredit perbankan melalui gugatan sederhana di Pengadilan Negeri Pinrang. Penelitian ini adalah penelitian empiris,Hasil penelitian menunjukkan bahwa penyelesaian sengketa fasilitas kredit perbankan melalui gugatan sederhana dengan Nomor perkara 9/Pdt.G.S/2021/PN.Pin di PT. BANK MEGA.Tbk. Memilih jalan penyelesaian sengketa melalui jalur perdamaian. Pada paktiknya ketika debitur melakukan kredit macet pihak PT. BANK MEGA.Tbk, dapat melakukan eksekusi atas dasar kesepakatan. Eksekusi yang dilakukan dengan cara: Pertama, dilakukan dengan somasi sebanyak tiga kali. Kedua, eksekusi dilakukan secara langsung penjualan dibawah tangan atas benda yang menjadi objek jaminan tanpa melalui gugatan ke pengadilan negeri. Ketiga, eksekusi langsung lewat pelelangan umum dimana hasil pelelangan tersebut diambil untuk melunasi pembayaran piutang. Eksekusi langsung bisa dilakukan tanpa melibatkan pengadilan. Jika dengan cara penjualan dibawah tangan mencapai harga tertinggi yang menguntungkan para pihak, maka penyelesaian sengketa jaminan fidusia sudah relevan dengan aturan hukum yang berlaku.